MANAJEMEN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL: BUDAYA SUKU GAYO - Juwandi, Juwandi; Zahriyanti, Zahriyanti; Yanti, Hera (Universitas Indraprasta PGRI, 2024)
This study aims to analyze character education management based on local wisdom in junior high schools in Ketol Subdistrict, Central Aceh. The approach used is qualitative with observation, interviews, and documentation methods. The research results show that the planning, implementation, organization, and control of character education based on local wisdom have been running well, although there are some supporting and inhibiting factors. Local wisdom-based character education has not been systematically planned as a specific program or curriculum, so it is only integrated into certain subjects such as Arts and Crafts. Challenges include the absence of specialized teachers to teach local wisdom values, lack of specific subjects, and the absence of funding allocation from the local government. Despite these challenges, school principals play a crucial role in coordinating character education programs and ensuring the active involvement of all parties. The internalization of local wisdom values is carried out simultaneously by teachers, most of whom are of Gayo ethnicity. The integration of local wisdom values such as togetherness, responsibility, and honesty into character education is important to shape a generation with identity and high morals. Implementation at the school and classroom levels includes advice, habituation, and exemplary behavior. This local wisdom-based character education is expected to have a positive impact on improving students' character in Ketol Subdistrict.